Determinant Factors Influencing Entrepreneurial Interest among Vocational School Students in Electronics Engineering - Hartati Hartati; Edy Supriyadi; Dedi Setiawan; Mustofa Abi Hamid; Muhammad Nurtanto; Muhammad Hakiki (International Journal of Engineering, Science and Information Technology, 2025)
This research investigates the various factors that affect entrepreneurial interest among vocational secondary school students enrolled in the electronics engineering program in Yogyakarta, Indonesia. The study identifies entrepreneurship as a crucial mechanism for fostering innovation, self-employment, and enhancing national competitiveness. It examines five primary determinants: self-efficacy, family support, entrepreneurial attitude, entrepreneurship education, and social and institutional support. A quantitative ex post facto methodology was utilized, involving 104 respondents chosen through proportional random sampling from three vocational institutions.  Data collection employed a validated four-point Likert scale questionnaire, with analysis conducted via simple and multiple linear regression techniques utilizing SPSS. The findings indicate that all five variables have significant and positive impacts on students' entrepreneurial interest, both independently and in combination. Entrepreneurship education and social–institutional support exhibit the most significant impact, underscoring the critical role of practical learning, mentorship, and supportive ecosystems in shaping entrepreneurial trajectories.  Self-efficacy and family support enhance motivation and confidence, while positive entrepreneurial attitudes promote perseverance and proactive engagement in opportunity recognition. These factors account for nearly half of the variance in entrepreneurial interest, thereby affirming the significance of the Theory of Planned Behavior and Social Cognitive Theory within vocational contexts. This study empirically enhances the discourse on entrepreneurship in technical and vocational education by highlighting the combined influence of psychological, familial, educational, and structural supports on the development of entrepreneurial intentions. Policy implications indicate that promoting entrepreneurship necessitates the alignment of curricular design, family involvement, and institutional policies to enhance entrepreneurial ecosystems within vocational education. Vocational schools can enhance student empowerment by fostering self-efficacy and offering accessible institutional resources, enabling the translation of entrepreneurial aspirations into sustainable ventures.